Paratelmatobius mantiqueira Pombal & Haddad, 1999 (Anura: Leptodactylidae): New specimens and rectification of the type locality of a rare species from the Serra da Mantiqueira, southeastern Brazil - Rotenberg, Elsie; Muscat, Edelcio; Stuginski, Daniel Rodrigues; Toledo, Luís Felipe; de Toledo Moroti, Matheus (Zootaxa, 2020)
There are currently seven species of small frogs (up to 30 mm in snout-vent length) in the genus Paratelmatobius Lutz & Carvalho 1958 (Frost, 2020). They are all endemic to mountain ranges in the Atlantic Forest, occurring in the Serra do Mar and Serra da Mantiqueira, southeastern Brazil (Santos et al. 2019). Most congeneric species are considered rare and their distribution is restricted to small areas (Domenico et al. 2014; Santos et al. 2020). Paratelmatobius mantiqueira Pombal & Haddad 1999 is one of the most enigmatic species in the genus. It hadn’t been seen from 1953, when the type series was collected, until 2005, when one specimen was found in the municipality of Resende, state of Rio de Janeiro (Vrcibradic et al. 2010). Recently, we found a new population of P. mantiqueira in the state of São Paulo. While reviewing the scattered information available about the species, we noticed inconsistencies related to the species’ type locality. We propose its rectification in this manuscript.